[tex]-x=-8\\x=8[/tex]
Answer:
x = 8
Step-by-step explanation:
The solution set of - x = -8 is x=8.
- x = -8 = x = 8
Write an equation in slope-intercept form for the line passing through the pair of points. (–1, 2), (4, –3)
Answer:
y = - x + 1
Step-by-step explanation:
The equation of a line in slope- intercept form is
y = mx + c ( m is the slope and c the y- intercept )
Calculate m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (- 1, 2) and (x₂, y₂ ) = (4, - 3)
m = [tex]\frac{-3-2}{4+1}[/tex] = [tex]\frac{-5}{5}[/tex] = -1, hence
y = - x + c ← is the partial equation
To find c substitute either of the 2 points into the partial equation
Using (- 1, 2), then
2 = 1 + c ⇒ c = 2 - 1 = 1
y = - x + 1 ← equation in slope- intercept form
The equation is y = –x + 1.
To find the slope-intercept form of a line passing through two points, calculate the slope using the given points and then use one point to find the y-intercept. The final equation for the line through the points (–1, 2) and (4, –3) is y = –x + 1.
To write an equation in slope-intercept form for the line passing through the points (–1, 2) and (4, –3), we first need to calculate the slope (m) using the formula
m = (y2 - y1) / (x2 - x1). Plugging in our points gives us m = (–3 – 2) / (4 – (–1)) = –5 / 5 = –1. Now that we have the slope, we can use one of the points to find the y-intercept (b). Using the point (–1, 2) and the slope-intercept formula y = mx + b, we plug in the values to get 2 = (–1)×(–1) + b, simplifying to 2 = 1 + b, which yields b = 1. Thus, the equation is y = –x + 1.
Can someone please explain this for me I’m
Not sure of the steps. See photo above
[tex]\bf \cfrac{x^8}{x^{14}}\implies x^8x^{-14}\implies x^{8-14}\implies x^{-6}\implies \stackrel{\textit{using the power rule}}{-6x^{-7}\implies \cfrac{-6}{x^7}}[/tex]
Question 1:
We have the following expression:
[tex]4x ^ {-4}[/tex]
By definition of power properties we have to:
[tex]a ^ {- 1} = \frac {1} {a ^ 1} = \frac {1} {a}[/tex]
Then, rewriting the expression:
[tex]\frac {4} {x ^ 4}[/tex]
ANswer:
[tex]\frac {4} {x ^ 4}[/tex]
Question 2:
For this case we have the following expression:
[tex]\frac {x ^ 8} {x ^ {14}} =[/tex]
By definition of power properties of the same base we have:
[tex]x ^ n * x ^ m = x ^ {n + m}[/tex]
Then, we can rewrite the denominator of the expression as:
[tex]\frac {x ^ 8} {x ^ 8 * x ^ 6} =[/tex]
Simplifying terms of the numerator and denominator:
[tex]\frac {1} {x ^ 6}[/tex]
ANswer:
[tex]\frac {1} {x ^ 6}[/tex]
What is the arc length of a quarter circle with a radius of 6 inches?
Arc length will be equal to the perimeter divided by 4 since we are talking about quarter circle.
[tex]2\pi r/4=\pi r/2=6\pi/2\approx\boxed{9.42}[/tex]
Hope this helps.
r3t40
Answer:
9.42 inches
Step-by-step explanation:
the cercle length is : 2π×r = 2×3.14 ×6=37.68 inches
the arc length of a quarter circle is : 37.68/4 =9.42 inches
The second termn in a geometric sequence is 20. The fourth termn in the same sequense is 45/4, or 11.225. What is the common ratio in this sequence?
Answer:
t2=ar^(2-1)
20=ar
then
t4=ar^(4-2)
45/4=ar.r
45/4=20.r
45/80=r
Answer:
r=±0.75
Step-by-step explanation:
Given:
a2= 20
a4= 45/4
As a geometric sequence has a common ratio and is given by:
an=a1(r)^n-1
where
an=nth term
a1=first term
n=number of term
r=common ratio
Now
a2=20=a1(r)^(2-1)
20=a1(r)^1
20=a1*r
Also
a4=45/4=a1(r)^(4-1)
45/4=a1r^3
(a1*r)r^2=45/4
Substituting value of 20=a1*r
(20)r^2=45/4
r^2=45/4(20)
r^2=0.5625
r=±0.75!
What is msu?
49°
77°
98°
161°
Answer:
77°
Step-by-step explanation:
[tex]\\ T = \frac{1}{2} (RU - SU)\\ \\ 21 =\frac{1}{2}(119 - SU)\\ \\ 42 = 119 - SU\\ SU=77[/tex]
The measure of mSU from the given diagram is 77 degrees
Circle geometryThe half of the difference of the intecepted arc is equal to the measure of the angle at the vertex
Applying this theorem to the given figure, we will havea;
1/2(119 - mSU) = 21
119 - mSU = 2(21)
119 - mSU = 42
Determine the measure of mSU
mSU = 119 -42
mSU = 77degrees
Hence the measure of mSU from the given diagram is 77 degrees
Learn more on geometry here: https://brainly.com/question/24375372
#SPJ5
The sum of two polynomials is 8d5 – 3c3d2 + 5c2d3 – 4cd4 + 9. If one addend is 2d5 – c3d2 + 8cd4 + 1, what is the other addend?
Answer:
The second polynomial is:
[tex]6d^5-2c^3d^2+5c^2d^3-12cd^4+8[/tex]
Step-by-step explanation:
Given
[tex]Sum\ of\ polynomials=S=8d^5-3c^3d^2+5c^2d^3-4cd^4+9\\Polynomial\ 1=A=2d^5-c^3d^2+8cd^4+1\\Polynomial\ 2=B=?\\S=A+B\\B=S-A\\=8d^5-3c^3d^2+5c^2d^3-4cd^4+9-(2d^5-c^3d^2+8cd^4+1)\\=8d^5-3c^3d^2+5c^2d^3-4cd^4+9-2d^5+c^3d^2-8cd^4-1\\=8d^5-2d^5-3c^3d^2+c^3d^2+5c^2d^3-4cd^4-8cd^4+9-1\\=6d^5-2c^3d^2+5c^2d^3-12cd^4+8[/tex]
Select one answer choice For part A and select one answer choice for part B
[tex]\bf \qquad \qquad \qquad \textit{discriminant of a quadratic} \\\\\\ \stackrel{\stackrel{a}{\downarrow }}{1}x^2\stackrel{\stackrel{b}{\downarrow }}{+6}x\stackrel{\stackrel{c}{\downarrow }}{+9}=0 ~~~~~~~~ \stackrel{discriminant}{b^2-4ac}= \begin{cases} 0&\textit{\underline{one real solution}}~~\textit{\Large \checkmark}\\ positive&\textit{two real solutions}\\ negative&\textit{no solution} \end{cases} \\\\\\ 6^2-4(1)(9)\implies 36-36\implies 0[/tex]
What is the value of x in the rhombus below?
Answer:
x = 17Step-by-step explanation:
We know:
1. Diagonals of a rhombus are perpendicular.
2. Diagonals divide the rhombus on four congruent right triangles.
3. The sum of measures of acute angles in a right triangle is equal 90°.
Therefore we have the equation:
(2x + 3) + (3x + 2) = 90 combine like terms
(2x + 3x) + (3 + 2) = 90
5x + 5 = 90 subtract 5 from both sides
5x = 85 divide both sides by 5
x = 17
The value of x is 17. This means that the angles formed by the diagonals of the rhombus are 37 degrees (2 * 17 + 3) and 53 degrees (3 * 17 + 2), and they indeed form congruent right triangles as required in the properties of a rhombus.
To find the value of x in the given equation, we start by understanding the properties of a rhombus and how its diagonals divide it into four congruent right triangles.
Given information:
Diagonals of a rhombus are perpendicular.
Diagonals divide the rhombus into four congruent right triangles.
Let's proceed with the steps to solve for x:
Step 1: Recognize that the angles formed by the diagonals are 2x + 3 and 3x + 2. Since these angles are congruent right angles, their sum is equal to 90 degrees.
Step 2: Set up the equation:
(2x + 3) + (3x + 2) = 90
Step 3: Combine like terms:
5x + 5 = 90
Step 4: Isolate x by subtracting 5 from both sides of the equation:
5x = 85
Step 5: Solve for x by dividing both sides by 5:
x = 85 / 5
x = 17
Hence, the value of x is 17. This means that the angles formed by the diagonals of the rhombus are 37 degrees (2 * 17 + 3) and 53 degrees (3 * 17 + 2), and they indeed form congruent right triangles as required in the properties of a rhombus.
To know more about triangles:
https://brainly.com/question/29083884
#SPJ6
The table below shows the future value of a certificate of deposit (CD), after x
years. Don states the applied interest is simple interest. True or false?
(number of years)
(future value)
$205.00
$210.00
$215.00
$220.00
$225.00
A. True
B. False
Answer:
A. True.
Step-by-step explanation:
The value increases by the same amount ($5) every year so it is simple interest.
Answer:True
Step-by-step explanation:
7+3 to the second power+(12-8) divided by 2x 4 is
[tex]\bf \stackrel{\mathbb{P~E~M~D~A~S}}{7+3^2+(12-8)\div 2\times 4}\implies 7+3^2+(\stackrel{\downarrow }{4})\div 2\times 4\implies 7+\stackrel{\downarrow }{9}+(4)\div 2\times 4 \\\\\\ 7+9+\stackrel{\downarrow }{2}\times 4\implies 7+9+\stackrel{\downarrow }{8}\implies \stackrel{\downarrow }{16}+8\implies 24[/tex]
Find the remainder when f(x) is divided by (x - k).
f(x) = 7x4 + 12x3 + 6x2 - 5x + 16; k = 3
Answer:
946
Step-by-step explanation:
To find just the remainder when dividing a polynomial by x-3, you could just plug in 3 into that polynomial.
If you were dividing by x+3, the remainder would just be the polynomial evaluated at x=-3.
Anyways plugging in 3 gives
7(3)^4 + 12(3)^3 + 6(3)^2 - 5(3) + 16
Just put this into your nearest calculator .
It should output 946.
You could use synthetic division or even long.
Synthetic Division.
We put 3 on outside because we are dividing by x-3.
3. | 7. 12. 6. -5. 16
| 21. 99. 315. 930
________________________
7. 33. 105. 310. 946
The remainder is the last number in the last column.
The plugging in and the synthetic division will always work when dividing by a linear expression.
If r(x) = 2 – x2 and w(x) = x – 2, what is the range of (Wºr) (x)
(-∞,0]
(-∞,2]
[0,∞)
[2,∞)
Answer:
(-inf,2]
Step-by-step explanation:
[tex](w \circ r)(x)=w(r(x))[/tex]
[tex]w(2-x^2)[/tex] I replaced r(x) with 2-x^2
[tex](2-x^2)-x[/tex] I replace the x in w(x)=x-2 with 2-x^2
[tex]-x^2-x+2[/tex]
You can graph this to find the range.
But since this is a quadratic (the graph is a parabola), I'm going to find the vertex to help me to determine the range.
The vertex is at x=-b/(2a). Once I find x, I can find the y that corresponds to it by using y=-x^2-x+2.
Comparing ax^2+bx+c to -x^2-x+2 tells me a=-1, b=-1, and c=2.
So the vertex is at x=1/(2*-1)=-1/2.
To find the y-coordinate that corresponds to that I will not plug in -1/2 in place of x into -x^2-x+2.
This gives me
-(-1/2)^2-(-1/2)+2
-1/4 + 1/2 +2
Find a common denominator which is 4.
-1/4 + 2/4 +8/4
8/4
2.
So the highest y value is 2 ( I know tha parabola is upside down because a=negative number)
That mean then range is 2 or less than 2.
So the answer an interval notation is (-inf,2]
Which of the following are valid names for the given triangle? Check all that apply.
Answer:
B,D, and E
Step-by-step explanation:
They all label the vertices in the correct order and do not label sides when naming it.
Answer:
B. [tex]\Delta TAX[/tex],
D. [tex]\Delta AXT[/tex]
E. [tex]\Delta XTA[/tex].
Step-by-step explanation:
We have been given a triangle. We are asked to choose the valid names for our triangle from the given choices.
We know that labels of the vertices of the triangle are used to name a triangle. In naming triangle, we can start from any vertex and we should keep the letters in order as we go around the triangle.
We can see that vertices of our given triangle are labeled as A, T and X, therefore, we can get three names for our triangle as:
[tex]\Delta TAX[/tex], [tex]\Delta AXT[/tex] and [tex]\Delta XTA[/tex].
Therefore, options B, D and C are correct choices.
what is the ratio of 12 minute to 1 hour
Answer:
12:1
Step-by-step explanation:
12:1Answer:
Step-by-step explanation:
(-b3 + 3b2 + 8) – ? - 5b2 – 9) = 5b3 +852 +17
Let's solve for x.
−b3+3b2+8−x−5b2−9=5b3+852+17
Step 1: Add b^3 to both sides.
−b3−2b2−x−1+b3=5b3+869+b3
−2b2−x−1=6b3+869
Step 2: Add 2b^2 to both sides.
−2b2−x−1+2b2=6b3+869+2b2
−x−1=6b3+2b2+869
Step 3: Add 1 to both sides.
−x−1+1=6b3+2b2+869+1
−x=6b3+2b2+870
Step 4: Divide both sides by -1.
−x
−1
=
6b3+2b2+870
−1
x=−6b3−2b2−870
Answer:
x=−6b3−2b2−870
Answer:
the answer is the first option -6b^3
Step-by-step explanation:
yup
please help! what is the value of x when f(x)=8? The graph shows the function f(x)=2^x
Answer:
[tex]f(x) = {2}^{x } \\ f(x) = 8 \\ \\ {2}^{x} = 8 \\ \\ {2}^{x } = {2}^{3} \\ \\ x = 3[/tex]
The value of x when f(x) = 8 is 3 in f(x) = 2^x
How to determine the value of x when f(x)=8?from the question, we have the following parameters that can be used in our computation:
f(x) = 2^x
To find the value of x when f(x) = 8, we need to solve the equation 2^x = 8.
We can rewrite 8 as 2^3
So, the equation becomes:
2^x = 2^3
Since the bases are the same, we can equate the exponents:
x = 3
Hence, the value of x when f(x) = 8 is 3.
Read more about function at
https://brainly.com/question/33401202
#SPJ3
a circular garden with a radius of 8 feet is surrounded by a circular path with a width of 3 feet. what is the approximate area of the path alone? use 3.14 for tt
Answer:
178.98 square feet
Step-by-step explanation:
Alright so we need to find two areas here and find the difference to find the area of the path.
The two shapes involved is a smaller circle inside a bigger circle.
Let's look at the smaller circle, the gardening area.
You are given is has a radius of 8 ft.
The area of a circle is [tex]\pi \cdot r^2[/tex] where r is the radius.
So the area of the smaller circle is [tex]\pi \cdot 8^2[/tex].
Now time to look at the bigger area (which will have some overlapping area with the smaller one which will subtract out to find the area of path).
The diameter of the smaller circle was (8+8)=16 feet.
What is the diameter of the bigger one. The path is 3 ft wide so we have to add a 3 before the diameter of the smaller circle to another 3 after that diameter to get the diameter of the bigger circle. So the diameter of the bigger circle is (3+16+3)=22 feet. The radius is half the diameter so the radius is 22/2=11.
The area of the bigger circle is [tex]\pi \cdot 11^2[/tex].
The area of the path=
the area of bigger circle - the area of smaller circle=
[tex]\pi \cdot 11^2-\pi \cdot 8^2[/tex]
Type this into your calculator with 3.14 instead of the [tex]\pi[/tex] button.
178.98 square feet
The answer is:
[tex]PathArea=178.98ft^{2}[/tex]
Why?To calculate the are of the path alone, we need to add the width of the path to the radius of the garden in order to know is radius, then, calculate the total area (using garden radius plus path width) and then, subtract it the area of the circular garden.
We know that the radius of the circular garden is equal to 8 feet, and the circular path has a width of 3 feet, so, the radius of the circular path will be:
[tex]CPath_{radius}=8feet+Path_{width}\\\\Path_{radius}=8feet+3feet=11[/tex]
Now, calculating the areas, we have:
Garden Area:
[tex]CircularGardenArea=\pi *radius^{2}\\\\CircularGardenRadius=\pi *8ft^{2}=3.14*64ft^{2}=200.96ft^{2}[/tex]
Total Area:
[tex]TotalArea=\pi *(8feet+3feet)^{2}=\pi *(11ft)^{2}=3.14*121ft^{2}=379.94ft^{2}[/tex]
Now, calculating the area of the path, we have:
[tex]TotalArea=CircularGardenArea+PathArea\\\\PathArea=TotalArea-CircularGardenArea\\\\PathArea=379.94ft^{2}-200.96ft^{2}=178.98ft^{2}[/tex]
Hence, we have that:
[tex]PathArea=178.98ft^{2}[/tex]
Have a nice day!
h(x)=2x-4/3
o h^-1(x)= 3x-12/2
o h^-1(x)= 3/(2x-4)
o h^-1(x)= 3x+4/2
Answer:
[tex]\large\boxed{h^{-1}(x)=\dfrac{3x+4}{2}}[/tex]
Step-by-step explanation:
[tex]h(x)=\dfrac{2x-4}{3}\to y=\dfrac{2x-4}{3}\\\\\text{Exchange x to y and vice versa}:\\\\x=\dfrac{2y-4}{3}\\\\\text{Solve for y:}\\\\\dfrac{2y-4}{3}=x\qquad\text{multiply both sides by 3}\\\\2y-4=3x\qquad\text{add 4 to both sides}\\\\2y=3x+4\qquad\text{divide both sides by 2}\\\\y=\dfrac{3x+4}{2}[/tex]
Which expression is equivalent to log3 c/9
log3c + logz(9)
log;(9) + log3
log3c - log3(9)
logg (9) - log:)
Answer:
log3c-log3(9) i.e. [tex]log_{3}c-log_{3}9[/tex]
Step-by-step explanation:
As per logarithmic relation
[tex]log_{base}\frac{A}{B}=log_{base}A-log_{base}B[/tex]
Now, in the given question base value is 3. Therefore
[tex]log_{3}\frac{c}{9}=log_{3}c-log_{3}9[/tex]
Hence the correct answer is third option.
The expression is equivalent to log₃ (c/9) is log₃ (c) - log₃ (9).
What is Logarithm?The power to which a number must be increased in order to obtain additional values is referred to as a logarithm. The easiest approach to express enormous numbers is this manner. Numerous significant characteristics of a logarithm demonstrate that addition and subtraction logarithms can also be written as multiplication and division of logarithms.
We have,
log₃ (c/9)
We know the from the property of logarithm
logₐ (c/d) = logₐ (c) - logₐ(d)
and, logₐ (cd)= logₐ(c) x logₐ (d)
So, log₃ (c/9)
= log₃ (c) - log₃ (9)
Learn more about Logarithm here:
https://brainly.com/question/30085872
#SPJ5
Find the value of 10!/(10-2)!
A) 720
B)80
C)90
D)45
Answer:
[tex]\huge \boxed{90}[/tex]
Step-by-step explanation:
First thing you do is subtract.
10-2=8
[tex]\displaystyle \frac{10!}{8!}[/tex]
Then you cancel the factorials.
[tex]\displaystyle \frac{10!}{8}=10\times9[/tex]
Multiply numbers from left to right to find the answer.
[tex]\displaystyle 10\times9=90[/tex]
[tex]\huge \textnormal{90}[/tex], which is our answer.
Hope this helps!
Final answer:
The value of 10!/(10-2)! simplifies to 90 after canceling out the common factorial terms, hence the correct answer is option C (90).
Explanation:
The expression 10!/(10-2)! represents a calculation involving factorials. The factorial of a number n is denoted n! and means the product of all positive integers from 1 up to n.
So, to simplify this expression, we can expand both factorials:
10! means 10 x 9 x 8 x 7 x 6 x 5 x 4 x 3 x 2 x 1,
and (10-2)! or 8! means 8 x 7 x 6 x 5 x 4 x 3 x 2 x 1.
When we divide 10! by 8!, the terms 8 x 7 x 6 x 5 x 4 x 3 x 2 x 1 (which is 8!) cancel out, leaving us with:
10 x 9 = 90.
Therefore, 10!/(10-2)! simplifies to 90, which is option C.
Given the following information, find the probability that a randomly selected student will be very short. Number of students who are very short: 45, short: 60, tall: 82, very tall: 21
Answer:
[tex]Pr=\dfrac{45}{208}\approx 0.216.[/tex]
Step-by-step explanation:
You are given the information about students:
45 students are very short;60 students are short;82 students are tall;21 students are very tall.In total, there are 45 + 60 + 82 + 21 = 208 students.
Use the definition of the probability:
[tex]Pr=\dfrac{\text{Number of favorable outcomes}}{\text{Number of all possible outcomes}}[/tex]
Number of favorable outcomes = 45
Nomber of all possible outcomes = 208,
hence,
[tex]Pr=\dfrac{45}{208}\approx 0.216.[/tex]
What does 3(8)+8 equal
Answer: 32
Step-by-step explanation: You need to use PEMDAS. First, multiply the two numbers.
3(8) = 24
Then, add 8.
24 + 8 = 32
32 is your answer.
can You show how to graph this
Answer:
The graph in the attached figure
Step-by-step explanation:
we have that
[tex]f(x)=x-4[/tex] ------> For [tex]x < 2[/tex]
[tex]f(x)=-2x+2[/tex] ------> For [tex]x\geq2[/tex]
To graph this piece wise- defined function
In the interval (-∞,2) ----> graph the line [tex]f(x)=x-4[/tex]
In the interval [2,∞) ----> graph the line [tex]f(x)=-2x+2[/tex]
The function is continue -----> the domain is all real numbers
using a graphing tool
see the attached figure
which trinomials are prime?
choose all answers that are correct.
Answer:
A C D
Step-by-step explanation:
A prime Trinomial is one that cannot be reduced into integer factors. It is easier to define a non prime trinomial first.
x^2 - 4x - 12 can be factored into
(x - 6)(x + 2) -6 and 2 are integers.
So B is not prime.
All of the others are prime. You need to use the quadratic formula to solve them.
B factors into
x^2 - 13x + 42
(x - 7)(x - 6)
Find P(not rolling 1, 3, 4, or 5) with one number cube.
The event "not rolling 1, 3, 4, or 5" is the same event as "rolling 2 or 6".
Since the possible outcomes of a number cube have the same probability, the probability of rolling 2 or 6 is given by
[tex]\dfrac{\text{\# of good outcomes}}{\text{\# of possible outcomes}}=\dfrac{2}{6}=\dfrac{1}{3}[/tex]
For one month Siera calculated her home town’s average high temperature in degrees Fahrenheit. She wants to convert that temperature from degrees Fahrenheit to degrees Celsius using the function . What does C(F) represent?
the temperature of F degrees Fahrenheit converted to degrees Celsius
the temperature of F degrees Celsius converted to degrees Fahrenheit
the temperature of C degrees Fahrenheit converted to degrees Celsius
the temperature of C degrees Celsius converted to degrees Fahrenheit
Answer:
The temperature of F degrees Fahrenheit converted to degrees CelsiusStep-by-step explanation:
[tex]C(F)=\dfrac{5}{9}(F-32)[/tex]
The function C(F) represents the temperature of F degrees Fahrenheit converted to degrees Celsius.
Explanation:The function C(F) represents the temperature of F degrees Fahrenheit converted to degrees Celsius. Temperature conversion is the process of converting between different temperature scales, such as Fahrenheit (°F), Celsius (°C), and Kelvin (K).
Each scale measures temperature differently, so conversions are necessary for various applications. The most common conversion formulas are: Celsius to Fahrenheit: °F = (°C × 9/5) + 32, and Celsius to Kelvin: K = °C + 273.15. These conversions are vital for international communication, weather reports, and scientific calculations.
Learn more about Temperature Conversion here:https://brainly.com/question/30451535
#SPJ12
Which expression is equivalent to 30 (1/2 x - 2) + 40(3/4 y-4)
Answer:
Step-by-step explanation:
Start by removing the brackets.
Left Brackets
30(1/2 x - 2)
30*1/2 x - 30*2
15x - 60
Right Bracket
40(3/4 y - 4)
40*3/4 y - 4*40
10*3 y - 160
30y - 160
Now put these 2 results together.
15x - 60 + 30y - 160 Combine the like terms.
15x + 30y - 220 That's one answer Others are possible.
5(3x + 6y - 44)
Answer:
74
Step-by-step explanation:
two numbers have the sum of 124 and a difference of 32. find the numbers.
Answer:
78 and 46
Step-by-step explanation:
Substitution (look it up it's hard to explain lol)
An alloy is a mixture of metals. Suppose that a certain alloy is made by mixing 50 grams of an alloy that 52% copper with 78 grams of pure copper. How many grams of copper are in the resulting mixture? What percent of the resulting mixture is copper?
Answer:
See below in bold.
Step-by-step explanation:
The 50 grams of alloy contains 50 * 0.52 = 26 g of pure copper.
So the amount of copper n the mixture = 78 + 26 = 104 g.
The total mass of the mixture = 78 + 50 = 128 g.
% copper = 104 * 100 / 128
= 81.25%.
Final answer:
The resulting mixture contains 104 grams of copper, which constitutes 81.25% of the mixture.
Explanation:
To find out how many grams of copper are in the resulting mixture of the alloy, we need to calculate the amount of copper from both sources and add them together. The first source is 50 grams of an alloy that is 52% copper, and the second source is 78 grams of pure copper.
50 grams of 52% copper alloy contains 50 grams × 0.52 = 26 grams of copper.78 grams of pure copper is of course 78 grams of copper.Now, add the amounts of copper from both sources:
26 grams (from the alloy) + 78 grams (pure copper) = 104 grams of copper.
To determine what percent of the resulting mixture is copper, we add the total weight of the mixture (50 grams + 78 grams = 128 grams) and then calculate the percentage:
(104 grams copper / 128 grams total) × 100 = 81.25%
So, the resulting mixture contains 104 grams of copper and is 81.25% copper.
Ship A receives a distress signal from the southwest, and ship B receives a distress signal from the same vessel from the north. At which location is the vessel in distress located? Describe how you arrived at your conclusion using complete sentences.
Answer:
ship B is going in a straight line north ship A is going diagonal make a straight line where each ship is moving towards and where ever they intersect will be where the ship in distress is located
hope this helped